Lung clearance index for monitoring early lung disease in alpha-1-antitrypsin deficiency. (July 2016) - Fuchs, Susanne I.; Schwerk, Nicolaus; Pittschieler, Klaus; Ahrens, Frank; Baden, Winfried; Bals, Robert; Fähndrich, Sebastian; Gleiber, Wolfgang; Griese, Matthias; Hülskamp, Georg; Köhnlein, Thomas; Reckling, Ludmilla; et al.
Abstract: Patients with alpha-1-antitrypsin deficiency (AATD) and a PI-ZZ genotype are at high risk to develop severe emphysema during adulthood. However, little is known about early stages of emphysema and disease manifestation in other PI-types. Spirometry is commonly used for monitoring although early manifestation of emphysema is suspected within the peripheral airways that are not accessible by forced expiratory manoeuvres. We hypothesized that the Lung Clearance Index (LCI) derived from multiple breath nitrogen-washout (N2 -washout) is useful to bridge this diagnostic gap. Patients from age 4 years onward and different PI-types performed N2 -washout and spirometry. Results were compared to controls. 193 patients (4–79 years, 75% PI-ZZ) and 33 controls (8–60 years) were included. Mean (SD) LCI in patients was 9.1 (3.1) and 6.3 (0.6) in controls ( p ≤ 0.001). 47% of adult patients with other than PI-ZZ genotypes and 39% of all patients with normal spirometry had abnormal LCIs. The LCI measured by N2 -washout discriminates between patients with AATD and controls, reflects AATD related lung disease in all stages and appears to identify early peripheral lung changes in younger age than spirometry. We conclude that a normal spirometry does not exclude presence of AATD related lung disease even in genotypes other than PI-ZZ. Highlights: Little is known about early stages of alpa-1-antitrypsin deficiency associated lung disease. Spirometry may not be sensitive to detect early changes. The Lung Clearance Index (LCI) measures ventilation inhomogeneity as a marker of early lung disease. This study compares LCI and spirometry in alpha-1-antitrypsin deficiency. We show that normal spirometry does not exclude presence of pulmonary changes in this population.